Increasing neutrophil-to-lymphocyte ratio following radiation is a poor prognostic factor and directly correlates with splenic radiation dose in pancreatic cancer. (May 2021) - Wolfe, Adam R.; Siedow, Michael; Nalin, Ansel; DiCostanzo, Dominic; Miller, Eric D.; Diaz, Dayssy Alexandra; Arnett, Andrea; Cloyd, Jordan M.; Dillhoff, Mary; Ejaz, Aslam; Tsung, Allan; Williams, Terence M.
Highlights: Neutrophil to lymphocyte ratio (NLR) is a marker of systemic inflammation and high ratios correlate with poor prognosis in cancers including pancreatic cancer. Neoadjuvant chemo-radiation is common treatment choice for locally advanced and borderline pancreatic cancer. In this study, the change in NLR from pre- to post-radiation (delta-NLR) correlated with poor surgical and clinical outcomes. High spleen dose was found to be a predictor of higher delta-NLR. Given these findings, the spleen should be considered an organ-at-risk for pancreatic cancer radiation planning. Abstract: Purpose: Neutrophil-to-lymphocyte ratio has been correlated with clinical outcomes in many cancers. We investigated whether the delta-NLR (ΔNLR) following radiation therapy (RT) could predict achieving surgical resection and the overall survival (OS) of patients with borderline resectable (BRPC) and locally advanced pancreatic cancer (LAPC), and whether the splenic radiation dose impacted ΔNLR. Methods/materials: 101 patients with biopsy-proven BRPC or LAPC who received induction chemotherapy followed by RT were retrospectively enrolled. Following contouring of spleens, dose-volume histograms (DVHs) for splenic dosimetric parameters were calculated. Pre- and post-RT complete blood counts (CBC) within two weeks were recorded. Delta (Δ) values were calculated by subtracting the post-RT value from the pre-RT value. Cox regression survival analysis for pre and postradiation CBC values and OS was performed. Receiver operating curves (ROC) were generated and optimal cutoff points for highest sensitivity and specificity were identified. Kaplan-Meier curves for OS were generated. Results: On univariate Cox regression analysis, the only significant CBC value associated with OS was ΔNLR (HR 1.06, CI 1.03–1.09, p  < 0.001). On multivariate analysis, ΔNLR, age, and completed resection all significantly predicted for worse OS ( p  < 0.05). ΔNLR significantly predicted achieving surgical resection ( p  = 0.04) and the optimal cutoff point for ΔNLR was 2.5. Patients with ΔNLR < 2.5 had significantly longer OS (log rank p  = 0.046). Spleen radiation dose parameters were all significantly higher in patients with a ΔNLR ≥ 2.5. Optimal radiation cutoff points to predict a ΔNLR ≥ 2.5 were splenic Dmean of 308 cGy and V5 of 10.3%. Conclusions: Among patients with BRPC or LAPC who have received induction chemotherapy, elevated ΔNLR after RT significantly predicts worse OS and decreased odds of achieving resection. Furthermore, ΔNLR is correlated with higher splenic doses, suggesting the spleen may be an important organ at risk.